Relationship between Countries’ Energy Indicators and the Indices of GVC Participation: The Case of APEC Member Economies - Elena Drobot; Ivan Makarov; Yelena Petrenko; Gaukhar Koshebayeva (Energies, 2022)
In the 21st century the importance of global value chains continues to grow. There is a scientific gap in the research on the relationship between countries’ energy indicators and the GVC participation indices. Based on the analysis of the APEC member economies’ GVC participation, the presence of quantifiable links between the countries’ energy indicators and GVC participation indices was identified. APEC member countries have a higher index of forward GVC participation compared to a rather low index of backward participation. We have confirmed the following hypotheses. Countries with higher energy consumption and countries exporting fuel have higher forward GVC participation. Energy importing countries and countries with higher energy intensity have higher backward GVC participation. Countries with higher energy intensity have lower forward GVC participation than countries with lower energy intensity. It was concluded that concerted efforts of APEC member economies are needed to increase GVC sustainability and develop unified energy policy standards. Managerial implications of energy efficient and sustainable GVCs will include competitive advantages growth for all the countries and suppliers participating in a particular GVC.